Development and Validation of a Motivation Scale for Status Pursuit by Organization Members - Wang, Zhicheng (Frontiers in Psychology, 2022)
Based on a literature review and questionnaire survey, the study proposes two tendencies of employees' status pursuit motivation. It applies exploratory factor analysis, confirmatory factor analysis, and other statistical methods to develop a scale of motivation for status which contains 9 items and 2 dimensions. This study expands the measurement methods of status research from a new perspective and lays a foundation for subsequent empirical research on organizational member status pursuit motivation.